2003
DOI: 10.1002/ejsp.177
|View full text |Cite
|
Sign up to set email alerts
|

Suppression and hypothesis testing: does suppressing stereotypes during interactions help to avoid confirmation biases?

Abstract: Recent work indicates that trying not to think in stereotypical terms increases the accessibility of stereotypical information, which paradoxically results in more stereotypical judgments. The present study translated the colour-blindness ideology in general and stereotype suppression research in particular into an hypothesis testing setting. Participants who were asked to suppress their stereotypes when selecting a set of questions were indeed less guided by ambient stereotypes than control participants, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Rather, we wanted to use this study to begin the process of examining hypothesis confirmation processes of the compensation effect. Accordingly, building on a well-established procedure in the research on hypothesis confirmation (Dumont et al, 2003;Snyder & Swann, 1978), we asked participants to select from among a set of questions that they would find most useful in gaining further information about the described group members. Our hypothesis was that the questions selected by participants would reflect the compensation effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, we wanted to use this study to begin the process of examining hypothesis confirmation processes of the compensation effect. Accordingly, building on a well-established procedure in the research on hypothesis confirmation (Dumont et al, 2003;Snyder & Swann, 1978), we asked participants to select from among a set of questions that they would find most useful in gaining further information about the described group members. Our hypothesis was that the questions selected by participants would reflect the compensation effect.…”
Section: Methodsmentioning
confidence: 99%
“…Questions. Participants learned that they had to create two questionnaires, one for the blue group and the other for the green group (for a similar procedure, see Dumont et al, 2003). The purpose of these questionnaires was ostensibly to gather further information about the two groups.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…Despite the great interest in social hypothesis testing, most research on this subject has focused on the investigation of personality traits and interpersonal impression formation, and only a few studies have adopted a group or intergroup perspective (Cameron & Trope, 2004; Dumont, Yzerbyt, Snyder, Mathieu, Comblain, & Scaillet, 2003; Leyens & Yzerbyt, 1992; Trope & Thompson, 1997). The aim of the present research was to investigate how social stereotypes affect the information‐gathering process of in‐group and out‐group members to determine if people adopt asymmetrical information search strategies.…”
Section: Introductionmentioning
confidence: 99%
“…We would also predict that the difference between the stereotypical and counter-stereotypical premises would decrease, if not disappear. However, several studies have shown that, when given instructions requiring them not to think in stereotypical terms, participants gave more stereotypical judgments, indicating that the accessibility of stereotypical information can increase under explicit instructions (Dumont et al, 2003;Macrae, Bodenhausen, Milne, & Jetten, 1994). If it is assumed that one of the effects of logical instructions is to promote processing of premises that is not sensitive to empirical knowledge, then we would be less certain about this second prediction.…”
Section: Studymentioning
confidence: 95%
“…This is a particularly interesting topic, since stereotypes strongly influence expectations of behaviour according to the group to which a subject belongs (Fiske, 2000;Leyens, Yzerbyt, & Schadron, 1994;Macrae & Bodenhausen, 2000). Research has shown that the influence of stereotypes is difficult to undo, even when explicit instructions are given (Dumont, Yzerbyt, Snyder, Mathieu, Comblain, & Scaillet, 2003). Thus understanding how people reason with stereotypes can provide some useful insights into the nature of the interaction between reasoning competence and non-logical factors postulated by dual-process theories.…”
Section: ) Université Du Québec à Montréal Canada and (2) Université mentioning
confidence: 99%